KETERAMPILAN MENGAJAR GURU DALAM PEMBELAJARAN DI RA KEBUN ILMU KECAMATAN SANGGAU LEDO - Herliyanti, Tri Nurul; Halida, Halida; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine teacher skills in learning in RA Kebun Ilmu Sanggau Ledo.. This study uses descriptive method with a qualitative approach. Data collection tools are interview guidelines, reporting and documentation. The results of the study show in skills and learning, the teacher performs the opening and closing activities of learning well. While the skill of explaining or explaining learning, the teacher has the ability to explain the material or use the media and explain clearly. Questioning skills in learning, the teacher has used clear and concise questions, the teacher also involves as many children as possible in ongoing learning. The skill to provide assistance in the lesson, the teacher is sufficient in giving encouragement, the teacher gives praise or defends to the child by verbal, not verbal, approach, giving good things or fun activities. The skills that are carried out in the classroom, the teacher has good skills, the teacher is visual or verbal visualization for the students of learning, the teacher explains to the students. Teacher Skills Hold Variations in Learning, the teacher has good enough skills, the teacher carries out various learning activities the teacher gives different activities. Skills to guide small group discussions, the teacher has the mind in a small group discussion well, the teacher focuses on the objectives and topics of discussion, the teacher leads the discussion to explain it. Skills to teach small groups and individuals in the lesson, the teacher has good skills in teaching small groups and individuals, the teacher shows warmth and sensitivity to the needs of children both in small groups and individuals, the teacher always listens simply to what children say in the lesson, the teacher also builds a trusting relationship in the child, the teacher responds positively to each child's opinion. Keywords: Teaching Skills, Learning